EFFECT OF FREQUENCY APPLICATIONS HaNPV TO THE PROTECTION OF PLANT TOMATO (Solanum lycopersicum) OF THE ORDER LEPIDOPTERA INSECT LARVAE ATTACK - Mardhiah, Ainal
Insects of the order Lepidoptera are a major pest on plants. These insects attack the horticultural and industrial crops such as tomatoes, onions, corn, soybeans, potatoes, spinach, cabbage, tobacco and cotton as well as cause massive damage, resulting in substantial losses for farmers. A common method used to control insect pests is to use synthetic insecticides. Such actions are not in accordance with the concept of Integrated Pest Management for the use of synthetic insecticides indiscretion can cause a variety of adverse effects, such as insect pest resistance and resurgence, the killing of non-target organisms, environmental pollution and human health problems due to residues on crops. Through his research, ITB has developed a virus-based biopesticide for controlling pest insects of the order Lepidoptera, which Helicoverpa armigera Nuclear Polyhedrosis Virus (HaNPV). This research study effectiveness of biopesticides in the field to determine the effect of the application frequency HaNPV tomato plant protection from insect larvae of the order Lepidoptera. This research was conducted in the field by applying five treatments, ie P1 = no use of synthetic insecticides and biopesticide (negative control) P2 = use of synthetic insecticides (positive control) P3 = use HaNPV with the frequency of application twice a week. P4 = use HaNPV with the frequency of application to once a week. P5 = use HaNPV with a frequency of once a month. Each treatment was repeated 50 times. The results of this study indicate that the use of HaNPV effective in controlling insect pests of the order Lepidoptera on tomato plants. As well as the use of synthetic insecticides, application HaNPV Lepidoptera pests effectively control insects and insect pests of the order Lepidoptera besides others. Tomato plants treated with synthetic insecticides indicate insect infestation with a level of 0,0000 / individual. Pest infestations value is not significantly different from the infestation of pests on tomato plants treated HaNPV twice a week, once every week, and once a month, the value of its pest infestations respectively are 0,0025 / individual, 0,0012 / individual and 0,0018 / individual. The use of HaNPV not effectively control pest insects of the order Lepidoptera besides. Values other than Lepidoptera insect infestation on tomato plants treated with synthetic insecticides is 8,6 / individuals, who significantly lower when compared with the value of pest infestation on tomato plants treated virus with a frequency of twice a week, once a week and every month their respective values are 11,66 /individual, 12,14 / 12,16/individual. The results also show that the use HaNPV effective against high growth of tomato plants. Tomato plants treated with synthetic insecticides show high growth rates of low crop plants is 0,0634 / day. High value crops with synthetic insecticide application was significantly different from that plant height HaNPV treated twice a week, once every week, and once a month, which is the average height of the plants of each crop is 0,0695 / day, 0,0740 / day and 0,0737 / day. As with synthetic insecticides, application HaNPV effectively reduce damage to tomatoes. Tomato plants treated with synthetic insecticides showed damage tomatoes with the level of damage 0 grams / plant. This value is not significantly different from tomato plants treated with HaNPV applications with a value of damage tomatoes are respectively 3,58 g / plant, 6,48 g / plant and 5,96 g / plant. HaNPV application against the order Lepidoptera infestation on tomatoes showed effective results that allows the tomato plant to grow and develop well and reproduce well.